Leksikon Jajanan Pasar Jawa Barat: Kajian Etnosemantik - Maulana Ghufar, Ahmad; Suhandano (UPA Bahasa Universitas Tidar And HISKI Kedu, 2022)
Local street foods are closely related to their cultural roots, thus the names of the food resemble their cultural identity. It is assumed that every name may have some background knowledge from its origin. This study aims to obtain an extensive description and classification of the lingual unit from West Java’s street foods. This research is an anthropological linguistic study using a descriptive qualitative method with an ethnosemantic approach. The result of this study shows 17 lingual unit data in the form of words, such as acronyms and original Sundanese words. Ten data were found in the form of attributive endocentric phrases which were classified into four parts. Those four parts are attributive phrases based on processing methods, regional origin, basic ingredients, and processed forms.